Pengaruh Saham Syariah Terhadap Pertumbuhan Ekonomi Nasional Tahun 2011-2021 - Rio, Rio Ramadhan Putra (Jurnal Ekonomi dan Keuangan Syariah, 2022)
The focus of this research is to determine the effect of Islamic stocks on economic growth in Indonesia. In this study, Islamic stocks are focused on the Indonesian Sharia Stock Index (ISSI) and national economic growth is measured by Gross Domestic Product (GDP) income. This type of research is quantitative research that emphasizes numerical data (numbers) processed using inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The data sources for this research are divided into two, inflation data obtained from the official website of the Central Bureau of Statistics and Bank Indonesia. Data processing in this study used the SPSS computer program and Microsoft Office Excel. Data analysis in this study used descriptive statistics, classical assumption tests, hypothesis testing, and simple linear regression analysis. The results of the study explain that there is a significant influence between Islamic stocks on national economic growth for the 2012-2021 period. Sharia stocks affect national economic growth by 87.1%. there is a positive or in-line relationship between Islamic stocks and national economic growth, the greater the value of Islamic stocks in the Islamic Capital Market, the higher the national economic growth in Indonesia. Vice versa, if sharia stocks decrease, national economic growth in Indonesia will also decrease.